Variability in the production of tannins and other polyphenols in cell cultures of 12 Nordic plant species - Suvanto J; Nohynek L; Seppänen-Laakso T; Rischer H; Salminen JP; Puupponen-Pimiä R (Springer Berlin Heidelberg, 2022)
MAIN CONCLUSION:
The polyphenol profiles of 18 cell cultures from 12 plant species were screened. The detected polyphenol fingerprints were diverse and differed from polyphenol profiles typically found in corresponding plant species. Cell cultures originating from 12 different plant species growing or grown in the Nordic countries were screened for their ability to synthesize polyphenols to assess their suitability for future studies and applications. The focus was on plant families Rosaceae and Ericaceae. On average, the Rosaceae cultures were the most efficient to produce hydrolysable tannins and the Ericaceae cultures were the most efficient to produce proanthocyanidins. This is in line with the general trend of polyphenols found in Rosaceae and Ericaceae leaves and fruits, even though several individual cell cultures differed from natural plants in their polyphenolic composition. Overall, several of the studied cell cultures exhibited capability in producing a large variety of polyphenols, including tannins with a high molecular weight, thus also showing promise for further studies concerning, for example, the accumulation of specific polyphenols or biosynthesis of polyphenols in the cell cultures.